KAJIAN BENTUK, FUNGSI, DAN MAKNA UNGKAPAN TRADISIONAL WACANA SORONG SERAH AJI KRAMA DI KABUPATEN LOMBOK BARAT DAN RELEVANSINYA DALAM PEMBELAJARAN MULOK DI SMP - sihwatik sihwatik (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
Abstract Sorong Serah Ajikrama text is a traditional idiom which is threathened with extinction. This is caused some factors, one of them because of the influence of globalization era and the high of technology. To prevent this condition, it needs an effort to preserve its. The aim of this traditional idiom description consist of form,function and meaning at west Lombok.the structural theory or function theory and semioyic theory which are released by some experts.The kind of this research is qualitative research. It explines the form, function, meaning and the steps in creating the learning matter in Junior High School (SMP). The description is done based on the numbers of traditional idiom of sorong serah ajikrama text in the whole Lombok Island (Sasaknesh) in general and specifically at West lombok. The method of this reserach is literature study and field study,interview, observation and recording. The result of this research will be useful for upgrading and adding the knowledge, as a reference for the other researchers whose relevance to this research.